Fiscal decentralisation to the sub-state local governments - Oommen, M.A. (2006)
Even after more than a decade of decentralised governance, the fiscal decentralisation scenario is disturbing. There is a decline in the percentage of local government expenditure in relation to the total government expenditure and in the progress of expenditure decentralisation in 11 out of the 15 major states. The revenue decentralisation trend is also no better and the average rate of growth in the tax revenue of panchayati raj institutions as well as the urban local bodies in most of the states has been negative. It renders efforts to build autonomous local governments impossible. - Reproduced.
Keywords: Local government